Differences in physical and technical performance characteristics between 11 v 11 chronological and bio-banded soccer match-play - Salter, J.; Forsdyke, D.; Arenas, L.; Dawson, Z.; King, M.; Myhill, N.; Robinson, J.; Towlson, C.; Springham, M.; Walsh, L.; Mallinson-Howard, S.; Barrett, S. (Journal of Science and Medicine in Sport, 2025)
Objectives Bio-banding groups athletes by biological maturity rather than chronological age, to reduce variation in physical characteristics, to promote more equitable competition and development opportunities. We investigated whether physical and technical performance characteristics differed between chronological and bio-banded 11v11 match-play formats in youth soccer. A secondary aim was to examine whether these differences varied by maturity status and timing.